Electrochemical sensing of amphetamine-type stimulants (pre)-precursors to fight against the illicit production of synthetic drugs. (20th December 2022) - Felipe Montiel, Noelia; Parrilla, Marc; Sleegers, Nick; Van Durme, Filip; van Nuijs, Alexander L.N.; De Wael, Karolien
Abstract: The illicit drug precursor market for the manufacture of amphetamine-type stimulants (ATS), mainly amphetamine, methamphetamine and methylenedioxymethamphetamine (MDMA), has emerged quickly in the last years. The evidence of a more complex and sophisticated drug market underlines the pressing need for new on-site methods to quickly detect precursors of synthetic drugs, with electrochemical analysis as a promising technique. Herein, the electrochemical fingerprints of ten common ATS precursors-3-oxo-2-phenylbutanenitrile (APAAN), 3-oxo-2-phenylbutanamide (APAA), methyl 3-oxo-2-phenylbutanoate (MAPA), benzyl methyl ketone (BMK), 1-(1, 3-benzodioxol-5-yl)propan-2-one (PMK), ephedrine, pseudoephedrine, safrole, sassafras oil and piperonal- are reported for the first time. The electrochemical screening disclosed the redox inactivity of BMK, which is an essential starting material for the production of ATS. Therefore, the local derivatization of BMK at an electrode surface by reductive amination is presented as a feasible solution to enrich its electrochemical fingerprint. To prove that, the resulting mixture was analyzed using a set of chromatographic techniques to understand the reaction mechanism and to identify possible electrochemical active products. Two reaction products (i.e. methamphetamine and 1-phenylpropan-2-ol) were found and characterized using mass spectrometry and electrochemical methods. Subsequently, the optimization of the reaction parameters was carefully addressed to set the portable electrochemical sensing strategy. Ultimately, the analysis concept was validated for the qualitative identification of ATS precursors in seizures from a forensic institute. Overall, the electrochemical approach demonstrates to be a useful and affordable analytical tool for the early identification of ATS precursors to prevent trafficking and drug manufacture in clandestine laboratories. Graphical abstract: Image, graphical abstract